Non-attendance in paediatric outpatient clinics, text reminder versus conventional system a randomised control trial - Fikry @ Fickry, Azri (2017)
INTRODUCTION: A high non-attendance rate (NAR) in outpatient clinics continues to pose a significant problem worldwide. A high NAR has negative consequences to costs of health care and quality of patient care. Hence, this study was undertaken to evaluate if SMS reminder could improve the NAR compared to the conventional system in a paediatric clinic at a tertiary hospital in East Coast Malaysia. Methods: We conducted a parallel single blind randomised controlled study where consented parents of patients that required a clinic appointment were recruited into the study. Upon randomisation, subjects were allocated either to the intervention group that will receive SMS reminder or the control group. In the intervention group, an SMS reminder will be sent a week before the appointment date but the control group will not be given any reminder.Results: 314 subjects were analysed in control group and 309 subjects for the intervention group. The NAR in our clinics was 33% and the SMS reminder significantly reduced the NAR in the intervention compared by 15.1% (p<0.001) to the conventional system. There was no association of poor socioeconomic group with poor attendance rate. Conclusion: SMS reminder was effective in reducing the NAR at Paediatric outpatient clinics compared to the conventional system. Poor socioeconomic status did not have any negative effect in attendance rate.